University–industry partnerships - Tapsir, Siti Hamisah (Penerbit UTM, 2010)
Universities are major players in the innovation system of both areas of performing research and training skilled personnel. It is now recognized that the generation of knowledge and its development into new technologies for commercialization can only be considered in line with the national innovation system and that the key to successful innovation is the flow of creativity, ideas, skills and people between players in the innovation system, namely the universities, public research institutes and private enterprises. Understanding this system can help identify leverage points for enhancing innovative performance and competitiveness. Knowledge transfer through R&D will no longer be an option but a necessity for survival in the business world especially in the areas of advanced technology and growing intellectual complexity. Due to this dependence on institutions of higher learning (IHLs), industry players need to keep abreast with IHLs to obtain the specific needs necessary to generate new income potentials that will spearhead the country's economy. Therefore, IHLs will have to forsake their image as ivory towers and work closely with the industries and vice versa, as the success of innovation will very much depend upon knowledge flow stimulated by such mechanisms as joint industry research, public/private sector partnerships, technology diffusion, shared infrastructure and movement of personnel through internship programmes. This in turn will provide a greater role of the industry players towards the enhancement of research, development and commercialization of technological innovation for the nation. As a result, there must exist strong networking amongst IHLs and industries as R&D should not be conceived by IHLs alone but importantly it must be done together with industries so that R&D products can become more marketable and meet the present and future demand of the nation. With the objective of understanding the needs of both academia and industry players towards fostering strategic university-industry linkages, a study commissioned by the Ministry of Higher Education (MOHE) to Universiti Teknologi Malaysia (UTM) has been conducted to address the issues and recommendations made by the government. The methodology is by desk study and review of publications, questionnaire surveys for IHLs and industries, meeting discussions and also through interviews of relevant parties dealing with human resource development and related university–industry liasons.